Constitutionality of Open Legal Policy Making Law Number 3 of 2022 Concerning the State Capital in the Perspective of Siyasa Dusturiyyah - Yasin al Arif, M.; Amri, Wahlulia; Dzil Arsyi Makiin, Inda (KnE Social Sciences, 2024)
Open legal policy is a mandate provided by the constitution related to broad and flexible regulations. However, this policy has the potential to be misused by lawmakers when making policies for the public. Therefore, repositioning is needed by examining the extent of the boundaries of open legal policy in the making of the National Capital Law. This study aims to identify issues of open legal policy and evaluate the substance of the National Capital Law from the perspective of Siyasah Dusturiyyah. This research is a normative legal study using secondary data viewed from the perspective of Siyasah Dusturiyyah using a conceptual approach. The research found that Siyasah Dusturiyyah in the substance of the National Capital Law needs evaluation, considering several notes that the Nusantara Capital (IKN) will be led by the IKN Authority Head. The appointment of the IKN Authority Head is based on appointment, not regional head election, which is a violation of democracy because the appointment of IKN leaders is not through elections, which means not accommodating the right to voice and the right to choose from the people, which also violates Islamic law. This research concludes that the open legal policy in the National Capital Law, from the perspective of Siyasah Dusturiyyah, can be an alternative solution in each legislator’s rules to ensure that the regulations made are in line to improve welfare and equalize the development in the regions. The involvement of local governments is needed to establish regional cooperation, involving community participation and the principles of openness and public interest. Keywords: constitutionality, open legal policy, ational capital, Siyasah Dusturiyyah